황해 중동부해역에서 CTD와 음향탐지기로 관측한 내부파와 표층 혼합 - 이상호; 최병주; 정우진; Lee, Sang-Ho; Choi, Byoung-Ju; Jeong, Woo Jin (Pada (Hanʼguk Haeyang Hakhoe), 2013)
Acoustic backscatter profiles were measured by Eco-sounder along an east-west section in the mid-eastern Yellow Sea and at an anchoring station in the low salinity region off the Keum River estuary in September 2012, with observing physical water property structure by CTD. Tidal front was established around the sand ridge developed in 50 m depth region. Internal waves measured by Eco-sounder during low tide period in the eastern side of the sand ridge were nonlinear depression waves with wave height of 15 m and mean wavelength of 500 m. These waves were interpreted into tidal internal waves that were produced by tidal current flowing over the sand ridge to the southeast. When weakly non-linear soliton model was applied, propagation speed and period of these internal depression wave were 50 m/s and 16~18 min. Red tides by Dinoflagelates Cochlodinium were observed in the sea surface where strong acoustic scattering layer was raised up to 7 m. Hourly CTD profiles taken at the anchoring station off the Keum River estuary showed the halocline depth change by tidal current and land-sea breeze. When tidal current flowed strongly to the northeast during flood period and land-breeze of 7 m/s blew to the west, the halocline was temporally raised up as much as 2 m and acoustic profile images showed a complex structure in the surface layer within 5-m depth: in tens of seconds the declined acoustic structure of strong and weak scattering signals alternatively appeared with entrainment and intrusion shape. These acoustic profile structures in the surface mixed layer were observed for the first time in the coastal sea of the mid-eastern Yellow Sea. The acoustic profile images and turbidity data suggest that relatively transparent low-layer water be intruded or entrained into the turbid upper-layer water by vertical shear between flood current and land breeze-induced surface current. 황해 중동부 해역에서 2012년 9월에 동서방향으로 설정된 단면과 금강 하구 외측 저염수 지역의 정박지점에서 음향탐지기를 이용하여 음향 후방산란 구조(acoustic backscatter profile)를 측정하였으며 CTD로 물성구조도 관측하였다. 수심 50 m 부근 해역에 발달한 해저사주 주변에서 조석전선이 형성되었다. 이 사주의 동쪽에서 저조 때 음향탐지기로 관측된 내부파는 파고가 약 15 m, 평균파장이 500 m정도이며, 파형이 비선형 오목형 파(depression wave)였다. 이 내부파는 남동쪽으로 흐르는 조류가 사주를 지나면서 만든 조석내부파로 해석되었다. 약한 비선형성 단독 내부파 이론을 적용하였을 때 오목형 내부파들의 전파속도는 약 50 cm/s 정도이고, 주기는 16~18분 정도로 계산되었다. 강한 음향 산란층이 국지적으로 7 m 정도 상승된 지역의 해면에서 Dinoflagelates Cochlodinium에 의한 적조가 관찰되었다. 금강하구 외측 정박지점에서 한 시간간격으로 관측한 물성구조는 해륙풍과 조류에 따른 염분약층 깊이 변동을 보여 주었다. 창조류가 북동쪽으로 강하게 흐르고 육풍이 서쪽으로 7 m/s 이상 불었을 때에는 염분약층이 일시적으로 상승하였고, 음향구조 영상은 해면 하 약 5 m까지 복잡한 구조를 보였는데 포획과 관입 형태를 갖는 강하고 약한 산란신호의 기울어진 음향구조가 수 십초 간격으로 교대로 나타났다. 표면 혼합층에서의 이러한 음향구조는 황해 중동부 연안역에서는 처음으로 관측되었다. 음향 후방산란 영상과 탁도 자료는 창조류와 육풍에 의한 표층 취송류가 만드는 수직적인 유속차(shear)에 의해 맑은 하층수가 탁한 상층으로 관입 혹은 포획된 것임을 제시한다.